Decreasing Tryptophan and Increasing Neopterin Plasma Levels During Pregnancy are Associated with High First Trimester Porphyromonas gingivalis K-Serotype IgG Serointensity in a Cohort of Hispanic Women - Postolache, Teodor T.; Upadhyaya, Sanjaya K.; Spector, Anna M.; Mohyuddin, Iqra; Constantine, Niel; Ernst, Robert K.; Wadhawan, Abhishek; Dutra, Samia V. O.; Dagdag, Aline; Makkar, Hina; Lowry, Christopher A.; Akram, Faisal; et al. (Current Topics in Medicinal Chemistry, 2022)
Background: Immune activation or high levels of stress may lead to increased metabolism of tryptophan during pregnancy. Porphyromonas gingivalis (Pg), the “keystone” periodontal pathogen, induces immune and indoleamine 2,3-dioxygenase (IDO) activation. Thus, we hypothesized that larger gestational decreases in tryptophan and elevations in neopterin and kynurenine would occur in pregnant women with elevated IgG antibodies to Pg capsular (K) serotypes. Methods: Venous blood of 52 Hispanic pregnant women with a mean age (SD) of 31.8 (5.9) years was sampled once per trimester of pregnancy (V1, V2, V3), and plasma was obtained and stored. ELISAs were used to measure Pg capsular (K) serotype IgG serointensity (V1 only) and neopterin levels (V1-V3). Tryptophan and kynurenine (V1-V3) were measured with high-performance liquid chromatography. The participants having IgG serointensity for any of the seven Pg K serotypes in the highest quartile were defined as the “High PgK_IgG” group and those having IgG serointensity for all K serotypes in the lowest three quartiles were defined as the “Low PgK_IgG” group. Statistics included multivariable linear and nonparametric methods. Results: Significant decreases in plasma tryptophan levels and increases in neopterin during gestation were found in “High PgK_IgG” women but not in “Low PgK_IgG” women. Kynurenine changes were not significantly different between the two groups. Conclusion: If replicated in larger studies and further characterized clinically, radiologically, and microbiologically, our results may potentially lead to novel interventional targets, as well as the development of more complete prognostic and predictive interactive biomarkers for adverse obstetrical outcomes and peripartum depression, and their prevention.
Keywords: IgG Serointensity